Bovine Tuberculosis Epidemiology in Cameroon, Central Africa, Based on the Interferon-Gamma Assay - Kelly, Robert F.; Gonzaléz Gordon, Lina; Egbe, Nkongho F.; Freeman, Emily J.; Mazeri, Stella; Ngwa, Victor N.; Tanya, Vincent; Sander, Melissa; Ndip, Lucy; Muwonge, Adrian; Morgan, Kenton L.; Handel, Ian G.; et al. (Frontiers in Veterinary Science, 2022)
Despite sub-Saharan Africa accounting for approximately 20% of the global cattle population, prevalence estimates and related risk factors of bovine tuberculosis (bTB) are still poorly described. The increased sensitivity of the IFN- assay, and its practical benefits, suggest the test could be useful to investigate bTB epidemiology in SSA. This study used a population-based sample to estimate bTB prevalence, identify risk factors and estimate the effective reproductive rate in Cameroonian cattle populations. A cross sectional study was conducted in the North West Region (NWR) and the Vina Division (VIN) of Cameroon in 2013. A regional stratified sampling frame of pastoral cattle herds produced a sample of 1448 cattle from 100 herds. In addition, a smaller cross-sectional study sampled 60 dairy cattle from 46 small-holder co-operative dairy farmers in the NWR. Blood samples were screened using the IFN- enzyme-linked immunosorbent assay (Prionics Bovigam®). Design-adjusted population prevalences were estimated and multivariable mixed-effects logistic regression models using Bayesian inference technques, identified risk factors for IFN- positivity. Using the IFN- assay, the prevalence of bTB in the dairy cattle was 21.7% (95% CI: 11.2-32.2). The design adjusted prevalence of bTB in cattle kept by pastoralists was 11.4% (95% CI: 7.6-17.0) in the NWR and 8.0% (95% CI: 4.7-13.0) in the VIN. Additionally, the estimates of the effective reproductive rate Rt were 1.12 for the NWR and 1.06 for the VIN, suggesting different transmission rates within regional cattle populations in Cameroon. For pastoral cattle an increased risk of IFN- assay positivity was associated with being male increasing herd size, exposure to bovine leucosis virus and paratuberculosis Decreased odds were associated with contacts at grazing, buffalo and increased contact with other herds. Few studies have used the IFN- assay to describe bTB epidemiology in SSA, specifically this study highlights the endemic situation of bTB in Cameroon and potential public health risks from dairy herds. Further work is needed to understand the IFN- assay performance, particularly in the presence of co-infections, and how this information can be used to develop control strategies in SSA contexts.